2010
DOI: 10.1017/s1368980010000649
|View full text |Cite
|
Sign up to set email alerts
|

Quality, but not cost, of diet is associated with 5-year incidence of CVD: the ATTICA study

Abstract: Objective: The aim of the present work was to calculate the current cost of the Mediterranean diet in Greece and to evaluate the role of diet cost in the development of cardiovascular events after a 5-year follow-up. Design: Cross-sectional. Cost of diet was measured in h/week based on common Greek dietary choices, while baseline dietary habits were assessed through a semiquantitative FFQ (Greek-EPIC). The Mediterranean Diet Score (MedDietScore) was applied to assess overall adherence to this pattern using sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Moreover, parents reported that due to financial constraints, a healthy diet was not always affordable. The cost of the Mediterranean diet is estimated to be rather rational for a middle-income household in Greece (Vlismas et al 2010), which might be not the case for families in low SES areas. Concerning the adherence to the Mediterranean diet, Mediterranean societies are rapidly withdrawing from this eating pattern, mainly due to influence from the Western diet patterns and the increasing prices of some of main Mediterranean diets' food items (Saulle et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, parents reported that due to financial constraints, a healthy diet was not always affordable. The cost of the Mediterranean diet is estimated to be rather rational for a middle-income household in Greece (Vlismas et al 2010), which might be not the case for families in low SES areas. Concerning the adherence to the Mediterranean diet, Mediterranean societies are rapidly withdrawing from this eating pattern, mainly due to influence from the Western diet patterns and the increasing prices of some of main Mediterranean diets' food items (Saulle et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…The ATTICA study [32] calculated the cost of the Mediterranean diet in Greece and evaluated the role of diet cost in the development of cardiovascular events after a five-year follow-up. The cost of the diet was measured in €/week based on common Greek dietary choices, while baseline dietary habits were assessed through a semi-quantitative FFQ.…”
Section: Discussionmentioning
confidence: 99%
“…One of the five articles conducted by Peracino et al [31] in their Appendix simply reported data from the study conducted by Dalziel et al [28], which had already previously been selected in the database search and, therefore, already included in the review, so the article conducted by Peracino et al [31] was excluded by the review. At the end of the selection process, only eight articles met the pre-determined criteria described above [28][29][30][32][33][34][35][36].…”
Section: Identification Of Relevant Researchmentioning
confidence: 99%
See 2 more Smart Citations